Collocations in the English LKS Books for Senior High School Students - Odilia Listya Alfiandita; Priyatno Ardi (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
This article investigates the types and variations of collocations used in English Lembar Kerja Siswa (LKS) books for senior high school students. The researchers employed corpus analysis in conducting this study. Data were collected from five English LKS books for grade X, XI, and XII Senior High School (SMA/SMK/MA). AntConc 3.5.8 was used to extract the data, which were then analyzed to find out the types and variations of collocations in the books. The findings revealed that the books consisted of Grammatical G1 (1804 tokens), Grammatical G2 (1 token), Grammatical G3 (423 tokens), Grammatical G4 (4664 tokens), Grammatical G5 (1 token), Grammatical G7 (34 tokens), Lexical L1 (3889 tokens), Lexical L3 (533 tokens), Lexical L4 (687 tokens), Lexical L5 (4 tokens), and Lexical L7 (2 tokens) collocations. Grammatical G4 collocation was mostly found in the LKS books. Furthermore, the collocation types in the English LKS books by grade levels were not various. The researchers suggest that English teachers should introduce collocations in their teaching to help the students to acquire the natural use of English.